Additive sustainability footprint: Rationale and pilot evaluation of a tool for assessing the sustainable use of PVC additives. Issue 2 (24th August 2019) - Everard, Mark; Blume, Richard
Abstract : PVC compounds contain additives necessary for processing and stability, and to modify the plastic's properties. The Europe‐wide VinylPlus® voluntary commitment includes a challenge to make progress toward sustainable use of additives. Additive Sustainability Footprint (ASF) was developed to assess sustainable use of additives across the whole societal life cycles of finished PVC articles, taking a risk‐based approach rather than simplistic hazard assessment. ASF addresses impacts across six life cycle assessment (LCA) stages established by ISO Standard 14040, using the four System Conditions (sustainability principles) developed by The Natural Step (TNS) covering social as well as environmental factors. For each LCA stage/System Condition combination, seven generically similar questions cover negative impacts (many covered by existing tools and regulations) but also the additive's positive contributions to the sustainability of finished articles. Positive contributions include ethical sourcing, longevity of service life, low maintenance inputs, and recyclability. Answers to questions determine a score, which can be combined across the life cycle and with other additives. Testing on a generic EU PVC window profile supported ASF development and demonstrated applicability and potential benefits including use for sensitivity analysis of alternative additives from different geopolitical regions or from recycled as opposed to virgin sources. J. VINYL ADDIT. TECHNOL., 26:196–208, 2020. © 2019 Society of Plastics Engineers